PGAM5-MAVS interaction regulates TBK1/ IRF3 dependent antiviral responses - Yu, Yidong; Zielinska, Marta; Li, Wei; Bernkopf, Dominic; Heilingloh, Christiane; Neurath, Markus; Becker, Christoph (Scientific Reports, 2020)
Viral infections trigger host innate immune responses, characterized by the production of type-I interferons (IFN) including IFNβ. IFNβ induces cellular antiviral defense mechanisms and thereby contributes to pathogen clearance. Accumulating evidence suggests that mitochondria constitute a crucial platform for the induction of antiviral immunity. Here we demonstrate that the mitochondrial protein phosphoglycerate mutase family member 5 (PGAM5) is important for the antiviral cellular response. Following challenge of HeLa cells with the dsRNA-analog poly(I:C), PGAM5 oligomers and high levels of PGAM5 were found in mitochondrial aggregates. Using immunoprecipitation, a direct interaction of PGAM5 with the mitochondrial antiviral-signaling protein (MAVS) was demonstrated. In addition, PGAM5 deficient cells showed diminished expression of IFNβ and IFNβ target genes as compared to WT cells. Moreover, PGAM5 deficient mouse embryonic fibroblasts (MEFs) exhibited decreased phosphorylation levels of IRF3 and TBK1 when challenged with poly(I:C) intracellularly. Finally, PGAM5 deficient MEFs, upon infection with vesicular stomatitis virus (VSV), revealed diminished IFNβ expression and increased VSV replication. Collectively, our study highlights PGAM5 as an important regulator for IFNβ production mediated via the TBK1/IRF3 signaling pathway in response to viral infection.
CRIS-Team Scopus Importer:2020-06-02